Thoracoscopic sympathectomy decreases disease burden in patients with medically refractory ventricular arrhythmias. (7th January 2022) - Lee, Andy Chao Hsuan; Tung, Roderick; Ferguson, Mark K
Abstract: OBJECTIVES: Thoracic sympathectomy has been shown to be effective in reducing implantable cardioverter-defibrillator (ICD) shocks and ventricular tachycardia recurrence in patients with channelopathies, but the evidence supporting its use for refractory ventricular arrhythmias in patients without channelopathies is limited. This is a single-centre cohort study of bilateral R1–R4 thoracoscopic sympathectomy for medically refractory ventricular arrhythmias. METHODS: Clinical information was examined for all bilateral thoracoscopic R1–R4 sympathectomies for ventricular arrhythmias at our institution from 2016 through 2020. RESULTS: Thirteen patients underwent bilateral thoracoscopic R1–R4 sympathectomy. All patients had prior ICD implant. Patients had a recent history of multiple ICD discharges (12/13), catheter ablation (10/13) and cardiac arrest (3/13). Ten patients were urgently operated on following transfer to our centre for sustained ventricular tachycardia. Seven patients had ventricular tachycardia ablations preoperatively during the same admission. Five patients were in intensive care immediately preoperatively, with 3 requiring mechanical ventilation. Three patients suffered in-hospital mortality. Kaplan–Meier analysis estimated 73% overall survival at 24-month follow-up. Among the 10 patients who survived to discharge, all were alive at a median follow-up of 8.7 months (interquartile range 0.6–26.7 months). Six of 10 patients had no further ICD discharges. Kaplan–Meier analysis estimated 27% ICD shock-free survival at 24 months follow-up for all patients. Three of 10 patients had additional ablations, while 2 patients underwent cardiac transplantation. CONCLUSIONS: Bilateral thoracoscopic sympathectomy is an effective option for patients with life-threatening ventricular arrhythmia refractory to pharmacotherapy and catheter ablation. Abstract : The sympathetic nervous system plays a prominent role in the genesis of many life-threatening ventricular arrhythmias.